Effects of Some Exposure Factors on Blood Lead Levels and its Relation to Childhood Anemia in Outpatient Children at Aljala Pediatric Hospital in Tripoli – Libya - Hassan, Tawfiq al-Mahdi; Abu Shnaaf, Hamida Ammari; Marwan, Arif Ghaith; Hwad, Ali Faraj (Journal of medical and pharmaceutical sciences, 2018)
The objectives of this study were to evaluate the effects of some exposure factors to lead and their relation to blood lead levels and childhood anemia. Blood samples of 160 child aged one month to eight years were collected in heparin containing tubes at outpatient clinic of Aljala Hospital in Tripoli – Libya during July – October 2009. Portions of the samples were used to estimate their hemoglobin levels; and the rest was kept at 4oC, until time for their lead contents determinations. A questionnaire was filled out by guardians to find the relation of some lead exposure factors to its levels in children’s blood samples. Such factors included the use of eye Kohol, type of residence area and the use of pottery and/ or porcelain utensils in food preparations or no. The results showed that; the levels of lead in the blood samples were 2.1 – 320 ug/ 100 ml. and for hemoglobin 5.5 – 14.7 g/ 100 ml blood. Comparing these lead levels with the lead toxicity limit of 10 ug/ 100 ml blood proposed by the Center of Disease Control and Prevention (CDC) of the USA; it was found that 74% of the children aged one month – < 1 year, 73% aged 1- < 2 years, 90% 2 – < 6 years and 81% aged 6 – 8 years had blood lead level > 10 ug/ 100 ml blood. Incidence of anemia among children with blood lead levels > 10 ug/ 100 ml were 46%, 36%, 42% and 45% for the age groups mentioned above respectively. In conclusion; there was no correlation (R = 6.0) and (P= 0.4) between blood lead levels and anemia. In addition; the results showed no effect of using pottery and/ or porcelain utensils in food preparation (P= 0.41) or living in the city or countryside (P= 0.284) on the blood lead levels. Therefore; more research is needed to define the sources or reasons for the elevated levels of lead in the childhood blood.